HONORING INNOVATORS. - O'Donnell, Alina (Literacy Today (2411-7862))
The article announces the winners of International Literacy Association (ILA) 2024 award which include Patricia A. Edwards has got William S. Gray Citation of Merit; Amber Lawson has got Dina Feitelson Research Award and Gwynne Ellen Ash has got Jerry Johns Outstanding Teacher Educator Award.